Transcriptomic and proteomic analysis of oil body associated protein dynamics in the biofuel feedstock Pennycress (Thlaspi arvense) - Luján, María Ángeles; Claver, Ana; Lorente, Patricia; López, M. Victoria; Alfonso, Miguel (Frontiers in Plant Science, 2025)
Pennycress (Thlaspi arvense) is an emerging feedstock for biofuel production because of its high seed oil content enriched in erucic acid. A combination of transcriptomic and proteomic tools was used to characterize the dynamics and relative abundance of the major oil body related proteins in the Pennycress seed. Our analysis identified 21 oleosins (OLE), 6 oil body associated proteins (OBAPs), 3 SEIPINS, 3 caleosins, 3 stereolisins and 3 lipid droplet associated proteins (LDAPs) in the Pennycress genome, showing high homology with respect to Arabidopsis or rapeseed. RNA-Seq analysis on five Pennycress seed maturation stages showed that most OLE and OBAP genes increased their expression with seed maturation, coinciding with the highest accumulation of triacylglycerol. Western-blot analysis of the OLE2 protein during seed maturation confirmed this result. However, OLE5 and SEIPIN1 genes showed higher expression at the early stages of seed maturation, suggesting that both proteins could be particularly involved in the initial stages of oil body formation. Proteomic analysis on oil body enriched fractions from the YELLOW and MATURE late seed maturation stages showed that all oleosin proteins were highly abundant in oil bodies. Caleosins and stereolisins were also highly abundant. Our results indicate the existence of differential expression patterns of oil body related genes during Pennycress seed maturation, suggesting different roles of these proteins for the formation and stabilization of oil bodies in the Pennycress seed.